Knowledge, attitude and practices towards research among undergraduate medical students in a teaching hospital, Trichy - Sivakumar, Aakhash; Nagendran, Mareeswaran (International Journal Of Community Medicine And Public Health, 2022)
Background: Late advancements in medicine and health care have made research an integral part of modern medicine, but research in most developing countries of the world is not a mandatory component of medical education, although it is well known that it has a positive effect on the quality of medical education. This study was conducted with an objective to assess the knowledge, attitude and practice towards research among undergraduate medical students. Methods: This is an Observational KAP study done among the undergraduate medical students in a teaching hospital Trichy. Around 200 students were selected from 2nd, 3rd, final MBBS students and Interns by Consecutive sampling method. Results: Among 200 study participants, 43% were females and 57% were males. Around 16% of the study participants were second year MBBS, 17%were final year MBBS part-I, 29% from the final year MBBS part-II and 38% (76) were interns. The overall percentages of knowledge, attitude and practice of the study participants in doing a medical research were 94%, 83% and 61% respectively. Conclusions: Encouraging medical students to engage in scientific research has shown excellent performance in daily clinical practice which requires multiple skills, and doctors who have had scientific training during their medical education may have an advantage over others when it comes to decision making using information collected from various resources.